Pendampingan Pemberdayaan Wanita Melalui Wirausaha Kain Batik Ecoprint di Wilayah Limo Depok - Pangestuti, Dewi Cahyani; Nastiti, Heni; Husniati, Renny; Sumilir, Sumilir (TAAWUN, 2023)
Empowering women and local economic development are crucial focal points in achieving sustainable and inclusive economic growth. A community engagement program with a focus on ecoprint batik training in Limo, Depok, employs a comprehensive approach encompassing outreach, training, mentoring, evaluation, and follow-up. By implementing these methods, it is expected that this community engagement program can attain its established goals. The objective of this community engagement initiative is to enhance the empowerment of women in the development of ecoprint batik enterprises. Through the application of outreach, training, mentoring, evaluation, and follow-up, participants are enabled to enhance product competitiveness and achieve economic self-sufficiency. The community engagement program in the Limo area of Depok has successfully achieved its goals of empowering women and promoting local economic development through the ecoprint batik enterprise. This program significantly contributes to the growth of the creative economy and the empowerment of women through home-based creative industry entrepreneurship. The outcomes of this program are expected to serve as a foundation for the development of similar initiatives in the future, aimed at further strengthening women's empowerment and fostering the growth of the creative industry in the region.